تقييم الخدمات الترفيهية في مدينة المجر الكبير لسنة 2020 - هاشم، أحمد صيهود; النجار، دنيا شكر عباس (جامعة ميسان - كلية التربية الأساسية, 2021)
Recreational and tourist areas are among the vital elements in the levels of urban planning because of their aesthetic and economic value, as recreational services represent a basic activity and an important requirement of life, as the demand for them increases as the number of the city's population increases, the research aims to know the types of entertainment services and their spatial distribution And the area that it occupies in the city of Hungary in addition to the extent to which this distribution of entertainment services corresponds to the population, in addition to knowing the extent of providing entertainment services in the city almajar alkabir according to the planning standards and laws adopted in Iraqi cities. Collecting data and information to learn about the reality of entertainment services in the city. The study found that the city almajar alkabir suffers from a clear decline in recreational services in terms of number and space allocated for recreational use, in addition to what it suffers from neglect in the field of administration, coordination, distribution and diversity, as well as the lack of basic services in public parks and parks. Considering the recreational services of the city, especially the public parks, as they are the natural outlet for the population, and working to achieve fairness in the distribution of services among the city's neighborhoods, as well as the constant concern and care for their maintenance and sustainability and keeping pace with the recent changes that happen to them.
تعد المناطق الترفيهية والسياحية من العناصر الحيوية في مستويات التخطيط العمراني لما لها من قيمة جمالية واقتصادية، إذ تمثل الخدمات الترفيهية فعالية أساسية ومطلبا مهما من متطلبات الحياة، فقد أخذ يزداد الطلب عليها كلما زاد عدد سكان المدينة، يهدف البحث إلى معرفة أنواع الخدمات الترفيهية وتوزيعها المكاني والمساحة التي تشغلها في مدينة المجر بالإضافة إلى مدى تناسب هذا التوزيع للخدمات الترفيهية مع عدد السكان، فضلا عن معرفة مدى توفير الخدمة الترفيهية في مدينة المجر بموجب المعايير التخطيطية والقوانين المعتمدة في المدن العراقية. لتحقيق أهداف الدراسة واختبار الفروض اعتمد الباحث على المنهج الوصفي التحليلي من خلال جمع البيانات والمعلومات للتعرف على واقع الخدمات الترفيهية في المدينة. توصلت الدراسة إلى أن مدينة المجر الكبير تعاني من تدني واضح في الخدمات الترفيهية من حيث العدد والمساحة المخصصة للاستعمال الترفيهي، فضلا عن ما تعاني من إهمال في مجال الإدارة والتنسيق والتوزيع والتنوع، كذلك انعدام الخدمات الأساسية في الحدائق العامة والمتنزهات، لهذا فقد أوصت الدراسة إلى إعادة النظر بالخدمات الترفيهية للمدينة وخاصة الحدائق العامة كونها المتنفس الطبيعي للسكان، والعمل على تحقيق العدالة التوزيعية للخدمات بين إحياء المدينة، فضلا عن الاهتمام والعناية المستمرة بصيانتها وإدامتها ومواكبة ما يطرأ عليها من تغيرات حديثة.
Keywords: التخطيط العمراني -- المنتزهات العامة -- التوزيع السكاني -- الترويح النفسي -- العراق